(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Having healthy eating in life is one of the fundamentals that our body needs; food becomes our comfort every time we might be having a hard time. Especially when we are dining outside our homes, like dining in a fancy restaurant, an expensive one, unlimited, eating all you can like a buffet, etc. Franchising your very own restaurant, like a grill, was one of the hardest things and decision-making to do. But, nowadays, Filipinos have been influenced by Korean culture, like the aforementioned “Samgyeopsal,” which was first introduced in the early 20th century in Kaesong, South Korea, as stated by Argarin’s (2021) article. Samgyeopsal Grill restaurant has been adopted in the Philippines, and it still had a significant number of consumers even when it first started. The result of this study is that the majority of the respondents are the younger generation, which is ages 18-35 years old, and for the civil status, most of the respondents are single and most likely employed consumers. The variable affecting the decreasing demand and continuous serving was the place when it came to “Wide parking space for the customers,” which was interpreted as partly satisfied. Meanwhile, the assessment in terms of product, price, and promotion was good enough for the two groups of respondents who were interpreted as very satisfied. The biggest problem encountered by the two groups of respondents was the long waiting time within the restaurant for the customers to eat and enjoy the food because of its small waiting area for a bunch of customers that are coming. Overall, the researchers recommend that a portion of the restaurant be renovated, particularly the area where customers can come in at any moment, because the number of customers may have an impact on restaurant operation.